Economic viability of REDD+ project in the Brasilian Amazonia - Plata Fajardo, Ana Milena; Timofeiczyk Junior, Romano; Silva, Zenobio Abel Gouvêa Perelli da Gama e; Silva, João Carlos Garzel Leodoro da; Juazeiro dos Santos, Anadalvo; Mosquera Agudelo, Paula Andrea (Instituto de Ecología, A.C., 2020)
This study aims to estimate the profitability and to evaluate the economic risks of REDD + projects in the Brazilian Amazon. The data were obtained through interviews and questionnaires to the proponents of the private REDD + projects of Amazonia. The economic risk was calculated using sensitivity analysis of the key project variables and the probability of project profitability through the Monte Carlo Simulation Method. The results indicate that the variable cost was responsible for 80% of the total costs. Fixed costs accounted for 20% of total costs. The result of the cash flow risk analysis concluded that REDD + projects in the Brazilian Amazon are viable, Internal Rate of Return of 11.49% a.a. was greater than the 10% a.a. Minimum Attractiveness Rate. The point at which the project computes a positive NPV is the price of BRL 18.6. Projects that sold VCUs at a price lower than BRL 18.6 may be financially unfeasible. The Monte Carlo simulation showed that the probability of obtaining a TIR of 10% a.a. or more is 51.53% a.a. It is concluded that REDD + projects in the Amazon have a positive return probability approaching 50%, but this return is not as attractive.